Enhanced tumor-targeted gene delivery by bioreducible polyethylenimine tethering EGFR divalent ligands1. (16th July 2015) - Lee, Duhwan; Lee, Yeong Mi; Kim, Jihoon; Lee, Myung Kyu; Kim, Won Jong
<x xml:space="preserve">Abstract</x> This work demonstrates successful delivery of a gene to EGFR-overexpressed cancer cells by using a rationally designed branched GE11 peptide as a targeting ligand.